Herleid de lettervormen
- \(-x-xy-2x-4xy\)
- \(-p-2q-p-4q\)
- \(b+4b^2-b\)
- \(2x+3y-3x-y+2x\)
- \(4q+3q^2+2q\)
- \(-3x+8x^2-2x\)
- \(xy-y+xy-4y-2xy\)
- \(-3c+7c^2-c\)
- \(-xy+y-2xy-4y-2xy\)
- \(-4c-3c^2+c\)
- \(-4q-6q^2-2q\)
- \(-4y+4y^2+2y\)
Herleid de lettervormen
Verbetersleutel
- \(\begin{align}-x-xy-2x-4xy&=-1.x-1.xy-2.x-4.xy\\&=-1.x-2.x-1.xy-4.xy\\&=-3x-5xy\\\\ \end{align}\)
- \(\begin{align}-p-2q-p-4q&=-1.p-2.q-1.p-4.q\\&=-1.p-1.p-2.q-4.q\\&=-2p-6q\\\\ \end{align}\)
- \(\begin{align} b+4b^2-b&=1.b+4.b^2-1.b\\&=1.b-1.b+4.b^2\\&=0b+4b^2\\ &=4b^2\\ \end{align}\)
- \(\begin{align}2x+3y-3x-y+2x&=2.x+3.y-3.x-1.y+2.x\\&=2.x-3.x+2.x+3.y-1.y\\&=x+2y\\\\ \end{align}\)
- \(\begin{align} 4q+3q^2+2q&=4.q+3.q^2+2.q\\&=4.q+2.q+3.q^2\\&=6q+3q^2\\\\ \end{align}\)
- \(\begin{align} -3x+8x^2-2x&=-3.x+8.x^2-2.x\\&=-3.x-2.x+8.x^2\\&=-5x+8x^2\\\\ \end{align}\)
- \(\begin{align}xy-y+xy-4y-2xy&=1.xy-1.y+1.xy-4.y-2.xy\\&=1.xy+1.xy-2.xy-1.y-4.y\\&=0xy-5y\\&=-5y\\ \end{align}\)
- \(\begin{align} -3c+7c^2-c&=-3.c+7.c^2-1.c\\&=-3.c-1.c+7.c^2\\&=-4c+7c^2\\\\ \end{align}\)
- \(\begin{align}-xy+y-2xy-4y-2xy&=-1.xy+1.y-2.xy-4.y-2.xy\\&=-1.xy-2.xy-2.xy+1.y-4.y\\&=-5xy-3y\\\\ \end{align}\)
- \(\begin{align} -4c-3c^2+c&=-4.c-3.c^2+1.c\\&=-4.c+1.c-3.c^2\\&=-3c-3c^2\\\\ \end{align}\)
- \(\begin{align} -4q-6q^2-2q&=-4.q-6.q^2-2.q\\&=-4.q-2.q-6.q^2\\&=-6q-6q^2\\\\ \end{align}\)
- \(\begin{align} -4y+4y^2+2y&=-4.y+4.y^2+2.y\\&=-4.y+2.y+4.y^2\\&=-2y+4y^2\\\\ \end{align}\)